Building and improving the capacity of fish and environmental health management strategy in Indonesia. Issue 1 (June 2020) - Lusiastuti, A M; Taukhid,; Maskur,; Murwantoko,; Prayitno, S B; Sugiani, D; Caruso, D
Abstract: Fish mortality due to outbreak and to the decrease in the quality of the environment is a latent problem increasingly complex in Indonesia. Extreme weather conditions with high rainfall intensity, reacute actually bring back several opportunistic pathogens of diseases such as Motile Aeromonads Septicemia. Various cases of mass fish deaths re-emerged, especially in public waters such as Maninjau Lake and Cirata reservoir is the sign of the decline in the quality and carrying capacity of the environment and it is suspected to be the main cause of the case. Over the past four years, fish mortality in public water has been regularly recorded and a peak of massive fish mortality occurred in 2016. A total of 4, 725 tons of dead fish occurred which is estimated around 0.95 percent of the total production of freshwater net cages cultivation nationally. This amount is estimated to cost economic losses up to IRD 47.25 billion equivalent to 3.3 million US (assuming the price of fish is IDR 10, 000/0.71US per kg). The occurrence of mass mortality of fish from net cages may reduce the aquaculture production originating from public waters up to 23.5 percent. Furthermore, risk of a new cross- border disease such as Acute Hepatopancreatic Necrosis Disease (AHPND); White Fecal Syndrome (WFS); Enterozytozoon hepatopenaei (EHP) and Tilapia Lake Virus (TiLV) heavily threaten aquaculture businesses. There is a need for cross-sectoral and even cross-country collaborative efforts, especially in anticipating the spread of cross-border fish diseases. This condition requires commitment and awareness from all stakeholders involved. Therefore, in order to promote sustainable aquaculture production, a national aquatic animal health (NAAH) strategy was formulated and will assist Indonesia government to: improve the national fish health services skills, make aware fish farmers undertaking responsible fish health management and to improve their capacity on emergency responses and contingency planning against diseases, reduce of important fish diseases and the use of chemicals in aquaculture, and prevent introduction of exotic disease. The implementation of the NAAH strategy needs guidance, support and full commitment from the government. The Ministry of Marine Affairs and Fisheries through Directorate General of Aquaculture is the competent authorities who will share responsibilities in the implementation of NAAH strategy.